A Convenient Way to do Valgus Osteotomy for Neglected Fracture Neck of Femur - Bansal, P; Singhal, V; Lal, H; Mittal, D; Arya, RK (Kathmandu University Medical Journal, 2015)
Background Neglected fracture of neck of femur in young adults is a major problem in developing countries. Existing treatment options varies from osteotomy to various graft techniques (muscle pedicle, vascularized and nonvascularized fibula etc.). There is paucity of literature regarding the use of double angle barrel plate and hip screw in such cases. We conducted a prospective longitudinal observational study with displaced, neglected fracture neck of femur in young adults and compared the results with literature. Objectives The aim of this study was to determine feasibility and effectiveness of 120° double angle barrel plate and hip screw fixation in neglected fracture neck of femur. Effectiveness of fixed 30 degree closed wedge osteotomy in neglected fracture neck of femur. Methods Thirty cases of neglected (more than three weeks) femoral neck fracture (Pauwel II and III) of age 20-60 years were included in the study conducted at Postgraduate Institute Of Medical Education and Research, Dr. Ram Manohar Lohia Hospital, New Delhi, India in year 2004-06. Average age of the patient was 35.4 years (range, 22yrs-55yrs). In all cases internal fixation was done by 120° double angle barrel plate and hip Screw. At the end of follow-up, results were evaluated according to Askin Bryan Criteria and Harris-hip score. Results Union was achieved in 28 of 30 patients. Two patients that went into nonunion were later treated with hemireplacement arthroplasty. According to Askin Bryan Criteria at the end of study, 35% patients had excellent results, 50% patients had good results. Minimum follow-up in our study was 12 months and maximum was five years. Conclusion This study validates the use of double angled screw plate configuration for successful outcome in patients with neglected fracture neck of femur. Valgus osteotomy is also technically easy operation in hands of average trauma surgeon with the use of a fixed angle plate and hip screw.DOI: http://dx.doi.org/10.3126/kumj.v11i2.12491 Kathmandu University Medical Journal Vol.11(2) 2013: 147-151